NEW TAXA AND NEW COMBINATIONS IN THE BRITISH FLORA - Rich, T. C. G.; McVeigh, A.; Stace, C. A. (Edinburgh Journal of Botany, 2018)
Four new taxa and nine new combinations are required for forthcoming floristic works by the authors. The new taxa are Centaurium tenuiflorum (Hoffmanns. & Link) Fritsch subsp. anglicum T.C.G.Rich & McVeigh, subsp. nov.; Centaurium × klattii P.Fourn. ex T.C.G.Rich, hyb. nov.; Centaurium × ubsdellii T.C.G.Rich, hyb. nov.; and Gentianella amarella (L.) Börner subsp. occidentalis T.C.G.Rich & McVeigh, subsp. nov. The new combinations are Centaurium erythraea Rafn var. latifolium (Sm.) T.C.G.Rich, comb. et stat. nov.; Gentianella amarella (L.) Börner subsp. anglica (Pugsley) T.C.G.Rich & McVeigh, comb. et stat. nov.; Aria parviloba (T.C.G.Rich) Sennikov & Kurtto, comb. nov.; Cotula sessilis (Ruiz & Pav.) Stace, comb. nov.; Elymus × drucei (Stace) Stace, comb. nov.; Elymus repens (L.) Gould f. aristatus (Schumach.) Stace, comb. nov.; Elymus athericus (Link) Kerguélen f. setigerus (Dumort.) Stace, comb. nov.; Ulmus minor Mill. subsp. cornubiensis (Weston) Stace, comb. et stat. nov.; and Dysphania ambrosioides (L.) Mosyakin & Clemants var. anthelmintica (L.) Stace, comb. nov.